Inhibiting Airway Smooth Muscle Contraction Using Pitavastatin: A Role for the Mevalonate Pathway in Regulating Cytoskeletal Proteins - Lu, Robin A.; Zeki, Amir A.; Ram-Mohan, Sumati; Nguyen, Nhan; Bai, Yan; Chmiel, Kenneth; Pecic, Stevan; Ai, Xingbin; Krishnan, Ramaswamy; Ghosh, Chandra C. (Frontiers in Pharmacology, 2020)
Despite maximal use of currently available therapies, a significant number of asthma patients continue to experience severe, and sometimes life-threatening, bronchoconstriction. To fill this therapeutic gap, we examined a potential role for the 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) inhibitor, pitavastatin. Using human airway smooth muscle (ASM) cells and murine precision-cut lung slices, we discovered that pitavastatin significantly inhibited basal-, histamine-, and methacholine (MCh)-induced ASM contraction. This occurred via reduction of myosin light chain 2 (MLC2) phosphorylation, and F-actin stress fiber density and distribution, in a mevalonate (MA)- and geranylgeranylpyrophosphate (GGPP)-dependent manner. Pitavastatin also potentiated the ASM relaxing effect of a simulated deep breath, a beneficial effect that is notably absent with the beta2-agonist, isoproterenol. Finally, pitavastatin attenuated ASM pro-inflammatory cytokine production in a GGPP-dependent manner. By targeting all three hallmark features of ASM dysfunction in asthma – contraction, failure to adequately relax in response to a deep breath, and inflammation – pitavastatin may represent a unique asthma therapeutic.